NMR spectroscopy derived plasma biomarkers of inflammation in human populations: Influences of age, sex and adiposity - Samantha Lodge; Reika Masuda; Philipp Nitschke; John P. Beilby; Jennie Hui; Michael Hunter; Bu B. Yeap; Oscar Millet; Julien Wist; Jeremy K. Nicholson; Elaine Holmes (PLoS ONE, 2025)
Understanding the distribution and variation in inflammatory markers is crucial for advancing our knowledge of inflammatory processes and evaluating their clinical utility in diagnosing and monitoring acute and chronic disease. 1H NMR spectroscopy of blood plasma and serum was applied to measure a composite panel of inflammatory markers based on acute phase glycoprotein signals (GlycA and GlycB) and sub-regions of the lipoprotein derived Supramolecular Phospholipid Composite signals (SPC1, SPC2 and SPC3) to establish normal ranges in two healthy, predominantly white cohorts from Australia (n = 398) and Spain (n = 80; ages 20–70 years). GlycA, GlycB, SPC1 and SPC3 were not significantly impacted by age or sex, but SPC2 (an HDL-related biomarker) was significantly higher in women across all age ranges by an average of 33.7%. A free-living Australian population cohort (n = 3945) was used to explore the relationship of BMI with the panel of inflammatory markers. The glycoprotein signals were directly associated with BMI with GlycB levels being significantly higher for women in all BMI classes. Conversely, SPC2 was found to be inversely associated with BMI and differed significantly between the sexes at each BMI category (normal weight p = 3.46x10-43, overweight p = 3.33x10-79, obese p = 2.15x10-64). SPC1 and SPC3 were markedly less affected by BMI changes. Given the significant association between SPC2 and sex, these data suggest that men and women should be modelled independently for NMR-determined inflammatory biomarkers, or that data should be corrected for sex.